OPTIMIZING HUMAN RESOURCE DEVELOPMENT IN VILLAGE ECONOMIC EMPOWERMENT: A CASE STUDY OF BUMDES BERSAMA BETARA: OPTIMIZING HUMAN RESOURCE DEVELOPMENT IN VILLAGE ECONOMIC EMPOWERMENT: A CASE STUDY OF BUMDES BERSAMA BETARA - Alhempi, R. Rudi; Yadi, Elmi; Febrina, Liga (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study aims to analyze the human resource (HR) development efforts at BUMDes Bersama Betara in Mekar Jaya, Tanjung Jabung Barat, in 2024, focusing on the implementation of educational and training methods. The research uses a qualitative descriptive approach, with data collected through interviews, observations, and documentation from key informants, including BUMDes managers and staff. The findings reveal that the educational method faced challenges due to poor communication and teamwork, leading to delays in daily operations and mishandling of customer goods. These issues stemmed from inadequate supervision and a lack of professionalism, where personal conflicts disrupted the development process. Similarly, the training method showed limited improvements, with persistent production errors and low employee initiative, primarily caused by fatigue and insufficient focus during work-hour training sessions. Overall, both HR development methods were found to be suboptimal, highlighting the need for future program adjustments, including clearer professional standards and better scheduling. This research provides insights for enhancing HR strategies in village-owned enterprises like BUMDes.